Behind the curve : science and the politics of global warming - Howe, Joshua P. (Weyerhaeuser environmental classics., 2014)
"In 1958, Charles David Keeling began measuring the concentration of carbon dioxide in the earth's atmosphere at the Mauna Loa Observatory in Hawaii. His project kicked off a half century of research that has expanded our knowledge of climate change. Despite more than fifty years of research, however, our global society has yet to find real solutions to the problem of global warming. Why? In Behind the Curve, Joshua Howe attempts to answer this question. He explores the history of global warming from its roots as a scientific curiosity to its place at the center of international environmental politics. The book follows the story of rising CO2--illustrated by the now famous Keeling Curve--through a number of historical contexts, highlighting the relationships among scientists, environmentalists, and politicians as those relationships changed over time. The nature of the problem itself, Howe explains, has privileged scientists as the primary spokespeople for the global climate. But while the "science first" forms of advocacy they developed to fight global warming produced more and better science, the primacy of science in global warming politics has failed to produce meaningful results. In fact, an often exclusive focus on science has left advocates for change vulnerable to political opposition and has limited much of the discussion to debates about the science itself. As a result, while we know much more about global warming than we did fifty years ago, CO2 continues to rise. In 1958, Keeling first measured CO2 at around 315 parts per million; by 2013, global CO2 had soared to 400 ppm. The problem is not getting better - it's getting worse. Behind the Curve offers a critical and levelheaded look at how we got here. Joshua P. Howe teaches history and environmental studies at Reed College."Scientists have proven to be right about the causes of a warming planet, but they have failed to stop the warming. Stopping it involves politics and economics more than science, and in this important book Joshua Howe examines how scientists and environmentalists--although both live in intensely political worlds--have managed to get the science right and the politics wrong. This is not the usual story of heroes and villains. Howe tells a more nuanced story-- a tragedy--in which a somewhat naive faith in science rendered scientists politically impotent in a complicated world. Few books published this year will tell a more important story."--Richard White, Margaret Byrne Professor of American History, Stanford"How shall we deal with climate change? That is not just an important topic but, from the standpoint of future generations, arguably the most important of all topics. Thorough and wide-ranging, this book puts the history of global warming policy in its full political and cultural context." - Spencer Weart, author of The Discovery of Global Warming"Behind the Curve is a much-needed book on the history of climate science and politics stretching back to the immediate post-World War II period." - Mark Carey, author of In the Shadow of Melting Glaciers"--